2012
DOI: 10.1002/app.37874
|View full text |Cite
|
Sign up to set email alerts
|

Anion exchange membranes derived from nafion precursor for the alkaline fuel cell: Effect of cation type on properties

Abstract: Highly stable hydroxide conducting membranes are necessary for solid-state alkaline fuel cells to have long performance lifetimes. In this study, we used solid-state chemistry to synthesize Nafion-based anion exchange membranes (AEMs) with a variety of covalently attached cations, including trimethylammonium, trimethylphosphonium, piperazinium, pyrrolidinium, pyridinium, and quaternized 1,4-diazabicyclo[2.2.2]octane. Infrared spectroscopy confirms a partial asymmetric functionalization of all cations with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 68 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…Recently, several studies have report on the perfluorinated AEMs from Nafion s or 3 M perfluorosulfonyl fluoride (PFSO 2 F) precursor via amination of the PFSO 2 F precursor with variety of covalently attached cations including trimethylammonium (TMA), 1, 4 -dimethylpiperazine (DMP), quaternized 1, 4-diazabicyclo [2.2.2] octane(DABCO) and guanidinium, and so on [22][23][24][25][26]28]. The F À form AEMs can be generated by the reaction of the 3 M or Nafion s precursor performed under rigorously anhydrous conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have report on the perfluorinated AEMs from Nafion s or 3 M perfluorosulfonyl fluoride (PFSO 2 F) precursor via amination of the PFSO 2 F precursor with variety of covalently attached cations including trimethylammonium (TMA), 1, 4 -dimethylpiperazine (DMP), quaternized 1, 4-diazabicyclo [2.2.2] octane(DABCO) and guanidinium, and so on [22][23][24][25][26]28]. The F À form AEMs can be generated by the reaction of the 3 M or Nafion s precursor performed under rigorously anhydrous conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Bosnjakovic et al also synthesized a polymer from 3M precursor, where they have identified the SO 2 stretching peak at 1467 cm −1 . Salerno et al used a modified Nafion® AEM . They have reported that the CF 2 stretch is observed around 1200 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Salerno et al used a modified Nafion ® AEM. 18 They have reported that the CF 2 stretch is observed around 1200 cm −1 . In addition to the literature related to perfluorinated AEM, we have referred to FTIR literature of Nafion ® as the polymers studied in this research are very similar to Nafion ® .…”
Section: Water Contentmentioning
confidence: 98%
See 1 more Smart Citation
“…See 13.66.222.141 Downloaded on 2019-04-08 to IP perfluorinated polymers and the carboxylate form of Nafion. [44][45][46] These membranes derived from commercially available precursors, still require further optimization for robust alkaline stability at elevated temperatures and for use in electrochemical devices with high current density operation.…”
Section: (B) (A)mentioning
confidence: 99%